1976
DOI: 10.1210/jcem-42-4-752
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Elevation of Plasma Melatonin and Urinary 5-Hydroxyindoleacetic Acid in Young Men: Attempts at Modification by Brief Changes in Environmental Lighting and Sleep and by Autonomic Drugs

Abstract: In order to determine whether the human pattern of circulating melatonin resembles that previously described in lower animals, men 19-32 years old were exposed to a light-dark cycle with 14 hours of light per day (L:D 14:10). In whites and blacks, nocturnal (dark phase, sleeping) melatonin levels were almost always elevated to 0.05-0.1 ng/ml plasma compared with lower or undetectable levels during the day, measured by the tadpole bioassay. Thin-layer migration of bioactive material was identical to that for me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
55
1
2

Year Published

1978
1978
1994
1994

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(67 citation statements)
references
References 24 publications
9
55
1
2
Order By: Relevance
“…The infusion o f isoproterenol into humans during the day is not followed by a commensurate rise in circulating melatonin levels [27], Perhaps the human pineal is similar to the hamster pineal, i.e., it may only possess the necessary receptors during the dark period.…”
Section: Discussionmentioning
confidence: 99%
“…The infusion o f isoproterenol into humans during the day is not followed by a commensurate rise in circulating melatonin levels [27], Perhaps the human pineal is similar to the hamster pineal, i.e., it may only possess the necessary receptors during the dark period.…”
Section: Discussionmentioning
confidence: 99%
“…( such as hippocampus and limbic system ) (Sapolsky et al, 1986) ; or they may stem from the imbalance among different neurotransmit= ters in the C.N.S., due to the selective impairment of noradrenergic pathways in aging (Hornykiewicz,1983). A clinically reliable tool to investigate the central noradrenergic tonus may be the study of melatonin circadian pattern, since the critica: melatonin secretion during the night is mediated by noradrenaline through the P -receptors (Reiter, 1976) and may bq selectively inhibited by f-adrenergic blociing drugs (Vaughan et al, 1976;Cowen et al, 1983). Our experience in this field concerns a croup of 14 clinically healthy women aged 66-90 y., in whom we simultaneously studied the circadian rhythm of plasma melato= nin, ACTH and cortisol, in order to investf;ate the relationships between melato= nin secretion and pituitary-adrenal axis in physiological aging.…”
Section: Discussionmentioning
confidence: 99%
“…Vaughan et al, (1976) and Weinberg et al, (1979) reported that having subjects sleep during the usual light period did not cause an increase in melatonin. However, lights were on during sleep in "those studies.…”
Section: I* I00mentioning
confidence: 99%
“…Both light and sleep seemed to contribute, but light was more important. As the melatonin cycle can be shifted by alterations in the light/ dark cycle but does not shift if light/dark is held constant and wake/sleep is shifted (Vaughan et al, 1976), melatonin cannot be the only controller of corticosteroid rhythm.…”
Section: Adrenal Glandmentioning
confidence: 99%